Control of root rot (Phytophthora cinnamomi) in avocado (Persea Americana) with bioagents - Sumida,Ciro Hideki (2020)
ABSTRACT Despite the favorable edaphoclimatic conditions for avocado production in Brazil, diseases such as root rot caused by the pathogen Phytophthora cinnamomi compromise the crop. With the aim of managing root rot in avocado, the present study aimed to evaluate chemical and biological control with isolates of Trichoderma spp. and Pseudomonas fluorescens. Thus, three assays were conducted to assess: (i) mycelial inhibition of P. cinnamomi by isolates of Trichoderma spp. and P. fluorescens from different crop systems; (ii) effect of autoclaved and non-autoclaved metabolites of P. fluorescens, and (iii) chemical or biological treatment of avocado seedlings on the control of root rot under field conditions. The isolates of Trichoderma spp. from maize cultivation soil and the commercial products formulated with Trichoderma presented greater antagonism (p <0.05) to the pathogen P. cinnamomi in the in vitro tests. Similarly, non-autoclaved metabolites of P. fluorescens presented antagonistic potential to control P. cinnamomi. Under field conditions, the fungicide metalaxyl and the bioagents showed effectiveness in controlling P. cinnamomi, as well as greater root length and mass. Results demonstrated potential for the biological control of avocado root rot with Trichoderma spp. and P. fluorescens.